Under pressure: a review of normal-tension glaucoma - MacDonald, Derek (Canadian Journal of Optometry, 2012)
On average, every third patient with glaucomatous optic neuropathy will present with intraocular pressure within the statistically normal range, manifesting normal-tension glaucoma. Eye care practitioners (and their patients) will benefi t from a familiarity with the diagnosis, treatment, and prognosis of this condition, including similarities to, and diff erences from, primary open-angle glaucoma, and the important roles played by the central nervous system and systemic vascular status.